2020
DOI: 10.1016/j.jad.2020.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fluctuations of emotional states in adolescents with delayed sleep phase—A longitudinal network modeling approach

Abstract: Background: Very late sleep rhythms are risks for social adjustment problems in adolescence.Using ecological momentary assessment data, we quantified and visualized temporal and contemporaneous within-persons dynamical relations of sleepiness and emotions in adolescents with and without late sleep rhythms. Methods:We analyzed a temporal network via multilevel vector autoregression (mlVAR) modeling and a contemporaneous network through the partial associations between the residuals of temporal and the between-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Studies used a range of technologies to collect active/subjective, passive/objective, and mixed (i.e., active/subjective and passive/objective) data. Studies employing passively/objectively collected data often produced predictive models with high accuracy in the detection of depression severity involving significant predictors such as geospatial movement, sleep duration, delayed sleep phase, circadian rhythm, audio features, language, accelerometer oscillation, and light exposure during bedtime [ 12 , 29 , 49 , 50 , 52 , 56 ]. Considering the type of technology, reviewed studies employed mobile technology (handheld IT devices such as smartphones, palmtops, tablets, laptops, etc.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies used a range of technologies to collect active/subjective, passive/objective, and mixed (i.e., active/subjective and passive/objective) data. Studies employing passively/objectively collected data often produced predictive models with high accuracy in the detection of depression severity involving significant predictors such as geospatial movement, sleep duration, delayed sleep phase, circadian rhythm, audio features, language, accelerometer oscillation, and light exposure during bedtime [ 12 , 29 , 49 , 50 , 52 , 56 ]. Considering the type of technology, reviewed studies employed mobile technology (handheld IT devices such as smartphones, palmtops, tablets, laptops, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Passive data collection via wearable technology, GPS, accelerometer/actigraph, Wi-Fi location, smartphone usage, and typing metadata Lower levels of physical activity were associated with increased levels of negative affect, depressive feelings, and anhedonia (e.g., reduced ability to enjoy pleasurable activities) Two studies employing non-clinical samples and GPS-derived data found no significant associations between these variables (Chow et al [ 30 ]; Melcher et al) [ 128 ] Social Functioning ( n = 21) Active data collection via self-reported questionnaires, and passive data collection via smartphone embedded audio features, and phone call/SMS frequency Increased levels of depression severity associated with preference for being alone, increased social distance, reduced closeness with other individuals, increased interpersonal stress, reduced speech duration, and reduced phone call and SMS frequency Depression severity showed an association with reliance on social expression such that higher reliance on social expression of feelings (i.e., anger) predicted a decrease in depression severity over time (Chue et al) [ 31 ] Moukaddam et al [ 136 ] used a clinical sample and found no correlations between depression levels and social interaction (SMS and phone call length and frequency) Sleep Quality ( n = 16) Assessment of sleep quality involved self-reported questionnaires, accelerometer inferences (e.g., total steps during bedtime), GPS-derived data, actigraphy, smartphone embedded light sensors (e.g., increased light exposure during bedtime), smartphone use (screen on/off), sound features (e.g., ambient silence), and heart rate (assessed via wearable technology) Most studies detected associations in variability of sleep quality and depression severity. Specifically, studies observed depression scores to be positively correlated with delayed sleep phase, sleep disturbance during weeknights, poor sleep quality, sleep variability, insomnia, and increased exposure to light during bedtime (Ben-Zeev et al [ 12 ]; Di Matteo et al, [ 49 ]; Difrancesco et al, [ 52 ]; Elovainio et al, [ 56 ]; Hung et al, [ 88 ]; Kaufmann et al, [ 100 ]; Kim et al, [ 105 ]; Melcher et al,) [ 128 ] Two studies (1 clinical and 1 non-clinical sample) did not find significant correlations between self-reports of sleep duration and depression (Difrancesco et al, [ 52 ]; Hamilton et al) [ 76 ]. Additionally, 2 studies using non-clinical samples found no significant associations in depression levels and sleep quality a...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of these examples also illustrate the usefulness of temporal network analyses for clinical applications, by suggesting key variables or symptom inter-relations to target in interventions. Although most of the temporal network articles so far have focused on clinical populations or research questions, others have investigated questions involving general emotion dynamics (Bringmann et al, 2013;Elovainio et al, 2020;Martín-Brufau et al, 2020;Meng et al, 2020) or even personality (Lazarus et al, 2020;Pavani et al, 2017).…”
Section: Auditing the Research Practices And Statistical Analyses Of Group-level Temporal Network Approach To Psychological Constructs: Amentioning
confidence: 99%